Decree of the Arab Republic of Egypt No. 69 of the Year 2015 Amending the Customs Tariff = قرار رئيس جمهورية مصر العربية بالقانون رقم 69 لسنة 2015 بتعديل التعريفة الجمركية / presidency - Egypt. presidency (2025)
Decree of the President of the Arab Republic of Egypt No. 69 of the year 2015 قرار رئيس جمهوري مصر العربية رقم 69 لسنة 2015 بتعديل التعريفة الجمركية